Transcatheter mitral valve replacement. Issue 6 (June 2021) - Enta, Yusuke; Nakamura, Mamoo
Highlights: Transcatheter mital valve (MV) replacement for failed bioprosthetic MV is well established and reasonable treatment option. Patient selection for transcatheter replacement of native MV remains challenging due to anatomical complexity of MV and peri-MV structure. Early feasibility studies of transcatheter devices for native MV replacement demonstrate the safety and are under transition to pivotal trials. Abstract: Transcatheter mitral valve (MV) repair, specifically the edge-to-edge leaflet repair, is a less invasive treatment of symptomatic mitral regurgitation (MR) in patients with high or prohibitive surgical risk. In cases with severe leaflet calcification, small mitral orifice area, and/or extremely wide regurgitation across the entire MV commissure, transcatheter MV repair may rather cause suboptimal or potentially hazardous outcomes. In these cases, MV replacement can be a more suitable option. Recently, percutaneous transcatheter MV replacement has emerged as an acceptable therapeutic option for the treatment of degenerated surgical bioprosthetic disease. Moreover, several transcatheter devices for native MV replacement are under evaluation with a hope to provide more complete and reproducible restoration of MV function. In this article, we will review current status, applications, clinical outcomes, and limitations that need to be overcome for transcatheter MV replacement for both degenerated surgical bioprosthetic disease and native MV disorders.